ANALISIS PERLAKUAN AKUNTANSI TERHADAP PERSEDIAAN BARANG USANG PADA PT. SINAR NIAGA SEJAHTERA (DISTRIBUTOR GARUDA FOOD) MANADO - Purba, Yelfindi; Karamoy, Herman; Warongan, Jessy D.L. (Universitas Sam Ratulangi, 2019)
Inventories of obsolete goods will incur inventory costs, costs that exceed income will not generate profits. PT. Sinar Niaga Sejahtera (Garuda Food Distributor) Manado quite often finds inventory obsolescence of goods sold on credit to customer outlets. The research objective was to analyze the causes of obsolete inventory and accounting treatment of obsolete inventory at PT. Sinar Niaga Sejahtera (Garuda Food Distributor) Manado in accordance with accounting theory. The research method used is descriptive qualitative, where data and information obtained from PT. Sinar Niaga Sejahtera (Garuda Food Distributor) Manado is described qualitatively. The results of research at PT. Sinar Niaga Sejahtera (Distributor of Garuda Food) Manado, which is the cause of obsolete inventory due to expiration of consumption or expiration periods and accounting treatment of inventory of obsolete goods using the reserve method is in accordance with the applicable accounting theory and has run well with and obsolete inventory still in the normal category because it never exceeds the limit of what is reserved for one period.